IMPLEMENTASI PERATURAN BUPATI NOMOR 65 TAHUN 2015 TENTANG PENEGAKAN DISIPLIN PEGAWAI - Syamsudin, Elby Rasyid Maladona; R.F.S, Harapan Tua; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2018)
Abstract: Implementation of Bupatl Regulation No. 65 of 2015 on Enforcing Employee DiscipHne. The purpose of this research is to know and analyze the implementation of Regent Regulation No. 65 of 2015 about the enforcement of employee discipline in the Public Works Department ofPelalawan Regency. The type of research is qualitative. The research informants are BKD, Satpol PP, Inspectorate and Secretary of Subag Umum Public Works Department of Pelalawan Regency. Data collection techniques are observation, interview and documentation. Data analysis uses interactive model, starting from data presentation, data reduction and conclusion. The results concluded that the implementation of Regent Regulation No. 65 of 2015 on enforcing discipline of employees in the Office of Public Works Pelalawan District is fluctuating or not maximized. While the factors influencing the implementation of Regent Regulation No. 65 of 2015 about the enforcement of personnel discipline in the Public Works Office of Pelalawan Regency are the factors of applying the sanction which is adi, political will factor, supervision factor and awareness factor.